Policy implementation for methicillin-resistant Staphylococcus aureus in seven European countries: a comparative analysis from 1999 to 2015. Issue 1 (1st January 2017) - Kinoshita, Takuya; Tokumasu, Hironobu; Tanaka, Shiro; Kramer, Axel; Kawakami, Koji
ABSTRACT: Background : Policies to reduce methicillin-resistant Staphylococcus aureus (MRSA) infections, both healthcare-acquired (HA-MRSA) and livestock-associated (LA-MRSA) are implemented Europe-wide, but evaluations are difficult for countries yet to implement such policies. A descriptive study was conducted, describing multinational MRSA rates and policy implementation, focusing on MRSA mandatory surveillance. We also investigated antibiotic use and MRSA rates and the use of veterinary antibiotics. Methods : This study used Europe-wide surveillance data on infectious diseases (EARS-Net), antibiotic consumption (ESAC-Net), and veterinary medicine (ESVAC). We visualized LA- and HA-MRSA related policies and MRSA rates from 1999 to 2015 in seven European countries. Changes in MRSA rates after implementation of an MRSA mandatory surveillance policy were investigated by setting each country as rate of 1.0 and compared countries with and without such policy. Correlations between antibiotic use and MRSA rates from 1999 to 2012 were investigated using defined daily dose. Sales data were used to investigate veterinary antibiotic use. Results : MRSA rates were 1–45.4% across the seven countries between 1999 and 2015. MRSA rates changed between 0.61 and 0.24 after the implementation of mandatory surveillance policies within a 6–12 year span. The rate of decrease rate in implemented and non-implemented countries ranged from 10% in Spain to 76% in the UK. The correlation between MRSA rate and cephalosporin consumption was r = 0.419, and for fluoroquinolones r = 0.305. Mean annual sales of veterinary cephalosporin and quinolone antibiotics were lowest in the UK (0.8 mg/PCU) and highest in Spain (9.7 mg/PCU) between 2009 and 2014. Conclusions : There were similar but different health policy implications in the seven countries regarding LA- and HA-MRSA. Although causation could not be defined, some policies such as mandatory surveillance may be helpful for countries that have yet to implement an MRSA policy. Further investigations are needed to evaluate each policies.